A Genre Analysis of English Supplementary Workbook for Seventh Grade - Nuraeni, Indah; Hidayat, Didin Nuruddin; Husna, Nida; Ersyad, Zakila Mardatila; Dinnisa Haura Zhafira Hidayat (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study investigates the alignment of a 7th-grade English workbook with the Merdeka curriculum syllabus, focusing on the representation of genre-based text components. Employing content analysis, the research examines the workbook's material against the syllabus requirements and genre analysis theory. The instruments used include the 7th-grade workbook, the Merdeka curriculum syllabus, and genre analysis frameworks. The findings reveal significant gaps in the workbook's content, particularly regarding the text structure of conversational and procedural texts, the minimal presence of language features, and the absence of explicit social functions. These shortcomings indicate that the workbook, in its current state, requires substantial improvement to effectively support English language learning in accordance with the Merdeka curriculum. The analysis concludes that the workbook only covers 40% of the competencies outlined in the syllabus. To ensure its suitability for classroom use, teachers need to develop supplementary materials that address the identified gaps and align with the curriculum's objectives.